1999
DOI: 10.1002/clc.4960220222
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis of mobile right atrial thrombi following severe pulmonary embolism

Abstract: Summary:Thrombolysis may favorably affect the clinical outcome of mobile right atrial thrombus following puimonary embolism (PE). We report the case of three patients with mobile right atrial thrombus following PE, in whom fibrinolysis was performed. Atrial mass disappeared on the control echocardiogram, but control ventilation perfusion scan showed new perfusion defects in all patients. Thrombolysis seems successful for the treatment of patients with mobile right atrial thrombus following PE; however, recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Studies showed that immediate thrombolytic therapy can resolve thrombi within 2 to 72 hours and normalize right ventricle function. 8,9,18 In our case, 4 out of 6 patients received streptokinase followed by heparin infusion. Two patients had contraindications for thrombolytic therapy and they received heparin infusion only.…”
Section: Discussionmentioning
confidence: 79%
“…Studies showed that immediate thrombolytic therapy can resolve thrombi within 2 to 72 hours and normalize right ventricle function. 8,9,18 In our case, 4 out of 6 patients received streptokinase followed by heparin infusion. Two patients had contraindications for thrombolytic therapy and they received heparin infusion only.…”
Section: Discussionmentioning
confidence: 79%
“…The effect of thrombolytic therapy on mortality is controversial. There are favorable results of thrombolytic therapy over heparin in patients with RHT associated PE in a small case series (10,13,(16)(17)(18)(19). First meta-analysis including 119 patients with RHT showed similar efficacy of all three treatment options (8).…”
Section: Discussionmentioning
confidence: 98%
“…In the event of mobile multiple intra-cardiac thrombi, surgery might not be a good choice for their complete removal. In these conditions, thrombolytic therapy might be preferable [8]. …”
Section: Discussionmentioning
confidence: 99%